Physical Activity for Cancer Patients During Covid-19 Pandemic: A Call to Action - De Moraes-Ferrari, G (Springer Science and Business Media Deutschland GmbH, 2021)
Self-isolation is strongly recommended for cancer patients during the COVID-19 pandemic, but may lead to physical inactivity and prolonged sitting time. The benefits of physical activity for cancer patients are manifold, such as reduced anxiety, fewer depressive symptoms, less fatigue, better quality of life, and improved physical function. In the last decade, several oncology-related organizations have provided guidance and summarized the evidence on the role of physical activity for cancer survivors. In this comment, we provide a brief summary of these recommendations and benefits of physical activity for cancer patients; and we recommend that oncologists and health practitioners should promote an active lifestyle for these patients during the pandemic and thereafter. Suggestions for implementing these actions in the clinical settings are also provided. © 2020, Springer Nature Switzerland AG.